High-transparency heat-insulation energy-saving window film master batch as well as preparation method and application thereof
By using modified nanotungsten bronze and conjugated polymers in window film masterbatches, the problems of insufficient light transmittance and poor infrared barrier effect of existing thermal insulation masterbatches are solved, and high transparency and excellent infrared barrier properties are achieved.
Patent Information
- Application Number
- CN202510183052.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-22
AI Technical Summary
The existing thermal insulation masterbatches are insufficient in light transmittance and have poor infrared barrier effects when applied to window films.
Using a highly transparent thermal insulation and energy-saving window film masterbatch, including modified nanotungsten bronze, ultraviolet absorber, dispersant and polymer carrier, the infrared barrier rate and optical properties are improved through structural modification of modified nanotungsten bronze and graft modification of conjugated polymers.
It significantly improves the light transmittance and infrared barrier rate of the window film masterbatch, ensures optical performance and mechanical strength, and improves the product's long-term service stability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a highly transparent heat-insulating energy-saving window film masterbatch and a preparation method and application thereof. Background Art
[0002] With global warming and increasingly tight energy supply, people are paying more and more attention to environmentally friendly, healthy and energy-saving lifestyles. Therefore, polymer materials with insulation and heat preservation properties are gradually gaining popularity. In the field of thermal insulation, coatings were commonly used to achieve thermal insulation effects, but coatings have many disadvantages. Therefore, thermal insulation masterbatches that can be directly added to the product production process came into being. However, the existing thermal insulation masterbatches have problems with insufficient light transmittance and poor infrared protection when used on window films. Therefore, it is necessary to study a new type of thermal insulation masterbatch to solve these problems. Summary of the invention
[0003] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a highly transparent heat-insulating and energy-saving window film masterbatch and a preparation method and application thereof, which can effectively improve light transmittance and infrared blocking rate.
[0004] In order to achieve the above purpose, one of the technical solutions adopted by the present invention is: a highly transparent heat-insulating and energy-saving window film masterbatch, which includes 1 to 50 parts of modified nano tungsten bronze, 1 to 5 parts of ultraviolet absorber, 1 to 10 parts of dispersant, and 35 to 100 parts of polymer carrier by weight; wherein the modified nano tungsten bronze includes a core structure and a shell structure coated on the surface of the core structure, the core structure is nano cesium tungsten bronze obtained by conjugated polymer grafting modification, and the shell structure is polyvinyl pyrrolidone; and the mass ratio of the core structure to the shell structure is 1:0.05~0.1.
[0005] The beneficial effects of the highly transparent heat-insulating and energy-saving window film masterbatch of the present invention are: The addition of modified nano tungsten bronze can improve the optical properties of window film masterbatch, the addition of ultraviolet absorber can improve the ultraviolet absorption capacity of window film masterbatch, the addition of dispersant can ensure the uniformity of window film masterbatch, and the addition of polymer carrier can ensure the mechanical strength of window film masterbatch; in modified nano tungsten bronze, nano cesium tungsten bronze has excellent visible light transmittance and infrared light absorption capacity due to its unique structural characteristics, and the large radius of cesium atom makes the surface defects of cesium tungsten bronze nanomolecules more, which can further enhance the infrared absorption capacity; then on the surface of nano cesium tungsten bronze Grafting conjugated polymers to form a core structure can utilize the conjugated structure of the conjugated polymer to further enhance the infrared absorption of nano-cesium tungsten bronze to improve its infrared blocking rate. In addition, the grafting of conjugated polymers to nano-cesium tungsten bronze can alleviate the problem of increased product haze and low light transmittance caused by the induced crystallization of cesium tungsten bronze. Polyvinyl pyrrolidone is then coated on the surface of the core structure to form a core-shell structure. The high light transmittance of polyvinyl pyrrolidone can be utilized to ensure the optical properties of the product, and the shell structure can be utilized to protect the core structure, so as to improve the long-term service stability of the product.
[0006] Furthermore, the conjugated polymer is selected from at least one of polystyrenes, polythiophenes, polyfluorenes, and polybenzothiophenes.
[0007] Specifically, the conjugated polymer is polystyrene with a molecular weight between 2000 and 5000. Polystyrene is rich in CC bonds and CH bonds, and can have a high emissivity in the 8-13 μm band, producing a radiation cooling effect to further enhance the thermal insulation effect of the product. Limiting the molecular weight of polystyrene to between 2000 and 5000 avoids the problem of infrared blocking and unclear visible light transmission caused by too low a molecular weight, and also avoids the problem of too high a molecular weight affecting the infrared absorption of cesium tungsten bronze and the mechanical properties of the polymer carrier. Furthermore, the structural formula of the nano cesium tungsten bronze is Cs x WO 3 , wherein 0.01≤x≤0.3; the mass ratio of the nano-cesium tungsten bronze and the conjugated polymer is 1:0.1~0.3.
[0008] Furthermore, the polymer carrier is at least one of polyethylene terephthalate, polyurethane, polyethylene, and polypropylene.
[0009] Furthermore, the ultraviolet absorber is at least one of UV-326 and UV-1577.
[0010] Furthermore, the dispersant is at least one of sodium tripolyphosphate, sodium hexametaphosphate, and sodium pyrophosphate.
[0011] The second technical solution adopted by the present invention is: a method for preparing any of the above-mentioned highly transparent heat-insulating and energy-saving window film masterbatches, comprising the following steps: (1) Dissolve an appropriate amount of silane coupling agent and nano-cesium tungsten bronze in ethanol, and adjust the pH value to between 7 and 9 with ammonia water; add the mixture to toluene after filtering, washing, and drying, and perform ultrasonic dispersion; then add conjugated polymer and azobisisobutyronitrile, and stir the mixture at a water bath temperature of 60 to 80°C to react; after the reaction is completed, filter, wash, and dry to obtain a core structure; (2) adding the core structure into ethanol for ball milling, then adding polyvinyl pyrrolidone, stirring evenly and then ultrasonically dispersing, and then centrifuging and drying to obtain modified nano tungsten bronze; (3) After the modified nano tungsten bronze, ultraviolet absorber, dispersant and polymer carrier are uniformly mixed, they are sent into a twin-screw extruder for melt extrusion granulation to obtain window film masterbatch.
[0012] The beneficial effects of the preparation method of the present invention are: In step (1), the uniformity of the dispersion of nano-cesium tungsten bronze is ensured by ultrasonic dispersion, so as to ensure the full reaction of nano-cesium tungsten bronze and conjugated polymer with the help of silane coupling agent and azobisisobutyronitrile; then, the core structure is ball-milled in step (2) to facilitate the core structure to contact with polyvinyl pyrrolidone in smaller particles, so as to facilitate the full coating of the core structure surface by polyvinyl pyrrolidone; finally, granulation is achieved in step (3). The window film masterbatch prepared by the preparation method of the present invention has excellent optical properties.
[0013] Furthermore, the preparation steps of the nano cesium tungsten bronze include: taking an appropriate amount of tungsten hexachloride and dissolving it in ethanol, adding cesium hydroxide and stirring for a period of time, and then adding acetic acid; then reacting at a temperature of 200-260°C for 12-24h, and after the reaction is completed, centrifuging, washing, and drying to obtain nano cesium tungsten bronze.
[0014] The third technical solution adopted by the present invention is: an application of any of the above-mentioned highly transparent heat-insulating and energy-saving window film masterbatches in window films. When the window film masterbatches of the present invention are applied to window films, they can enhance the heat-insulating performance of the window films and ensure the optical performance of the window films. DETAILED DESCRIPTION
[0015] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. It should be noted that the following embodiments are for a better understanding of the present invention, are not limited to the best embodiments, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0016] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0017] In addition, if the specific experimental steps or conditions are not specified in the examples, the operations or conditions of the conventional experimental steps described in the literature in the art can be carried out. The numerical ranges shown by "~" in the examples indicate the ranges containing the values recorded before and after "~" as the minimum and maximum values, respectively. If the manufacturers of the reagents or instruments are not specified, they are all conventional reagent products that can be obtained commercially.
[0018] The highly transparent heat-insulating and energy-saving window film masterbatch of the present invention comprises, by weight, 1 to 50 parts of modified nano tungsten bronze, 1 to 5 parts of ultraviolet absorber, 1 to 10 parts of dispersant, and 35 to 100 parts of polymer carrier; wherein the modified nano tungsten bronze comprises a core structure and a shell structure coated on the surface of the core structure, the core structure is nano cesium tungsten bronze obtained by grafting modification with a conjugated polymer, and the shell structure is polyvinyl pyrrolidone; and the particle size of the nano cesium tungsten bronze is not greater than 50 nm, and the mass ratio of the core structure to the shell structure is 1:0.05 to 0.1. By grafting a conjugated polymer on the surface of nano-cesium tungsten bronze to form a core structure, the conjugated structure of the conjugated polymer can be used to further enhance the infrared absorption of the nano-cesium tungsten bronze to improve its infrared blocking rate, and the grafting modification of the conjugated polymer on the nano-cesium tungsten bronze can alleviate the problem of increased product haze and low light transmittance caused by the induced crystallization of cesium tungsten bronze; and then polyvinyl pyrrolidone is coated on the surface of the core structure to form a core-shell structure, which can not only use the high light transmittance of polyvinyl pyrrolidone to ensure the optical performance of the product, but also use the shell structure to form a protective effect on the core structure, so as to improve the long-term service stability of the product.
[0019] In some embodiments, the conjugated polymer is selected from at least one of polystyrene, polythiophene, polyfluorene, and polybenzothiophene. Furthermore, the conjugated polymer is a polystyrene with a molecular weight between 2000 and 5000. Since polystyrene is rich in CC bonds and CH bonds, it can have a high emissivity in the 8-13 μm band, producing a radiation cooling effect to further enhance the thermal insulation effect of the product. Limiting the molecular weight of polystyrene to between 2000 and 5000 avoids the problem of infrared blocking and unclear visible light transmission caused by too low a molecular weight, and avoids the problem of too high a molecular weight affecting the infrared absorption of cesium tungsten bronze and the mechanical properties of the polymer carrier. In some embodiments, the structural formula of nano cesium tungsten bronze is Cs x WO 3 , where 0.01≤x≤0.3; the mass ratio of nano-cesium tungsten bronze and conjugated polymer is 1:0.1~0.3. Due to its unique structural characteristics, nano-cesium tungsten bronze has excellent light transmittance and infrared light absorption capabilities. In addition, the cesium atomic radius is large, and the surface defects of cesium tungsten bronze nanomolecules are more, which can enhance its own infrared absorption ability and further improve the optical performance.
[0020] In some embodiments, the polymer carrier is at least one of polyethylene terephthalate, polyurethane, polyethylene, and polypropylene. The ultraviolet absorber is at least one of UV-326 and UV-1577. The dispersant is at least one of sodium tripolyphosphate, sodium hexametaphosphate, and sodium pyrophosphate.
[0021] The present invention also provides a method for preparing a highly transparent heat-insulating energy-saving window film masterbatch, comprising the following steps: Preparation of nano-cesium tungsten bronze powder: Take an appropriate amount of tungsten hexachloride and dissolve it in ethanol, add cesium hydroxide and stir for a period of time, then add acetic acid; then react at a temperature of 200-260°C for 12-24h. After the reaction is completed, centrifuge, wash and dry to obtain nano-cesium tungsten bronze powder; Preparation of modified nano tungsten bronze: dissolve an appropriate amount of silane coupling agent (such as methacryloxypropyl trimethylsiloxane) and nano cesium tungsten bronze in ethanol, and adjust the pH value to between 7 and 9 with ammonia water; add toluene after filtering, washing, and drying, and perform ultrasonic dispersion; then add polystyrene and azobisisobutyronitrile, and stir the reaction at a water bath temperature of 60 to 80°C. After the reaction is completed, filter, wash, and dry to obtain a core structure; add the core structure to ethanol for ball milling, then add polyvinyl pyrrolidone, stir evenly, perform ultrasonic dispersion, and then centrifuge and dry to obtain the modified nano tungsten bronze; Preparation of window film masterbatch: After the modified nano tungsten bronze, UV absorber, dispersant and polymer carrier are mixed evenly, they are sent to a twin-screw extruder for melt extrusion granulation to obtain the window film masterbatch. The aspect ratio of the twin-screw extruder is not less than 40:1, the extrusion temperature is 240~270℃, and the length of the window film masterbatch is 3mm±1mm and the diameter is 2.5mm±1mm.
[0022] Example 1 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 23g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 6.3g of polystyrene and 4.6g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 70°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 1.5g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain the modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium hexametaphosphate and polyurethane were mixed evenly in a ratio of 30:3:5:70, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0023] Example 2 The window film masterbatch was prepared according to the following preparation method: Take 12.3g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 4g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 200℃ for 20h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 24g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 8g of polystyrene and 5.1g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 80°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 2g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain the modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium tripolyphosphate and polyethylene terephthalate were uniformly mixed in a ratio of 35:3:5:60, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0024] Example 3 The window film masterbatch was prepared according to the following preparation method: Take 8.5g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 2.7g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 250℃ for 13h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 18g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 5.6g of polystyrene and 4g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 60°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 1.2g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain the modified nano-tungsten bronze; The modified nano tungsten bronze, UV-1577, sodium pyrophosphate and polypropylene were uniformly mixed in a ratio of 26:2.5:7:70, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0025] Example 4 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 23g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 6.3g of polystyrene and 4.6g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 70°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 1.5g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain the modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium hexametaphosphate and polyurethane were mixed evenly in a ratio of 35:3:5:65, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0026] Example 5 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 23g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 6.3g of polystyrene and 4.6g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 70°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 1.5g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain the modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium hexametaphosphate and polyurethane were mixed evenly in a ratio of 30:2:8:70, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0027] Example 6 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 23g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 6.3g of polystyrene and 4.6g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 70°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 1.5g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain the modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium hexametaphosphate and polyurethane were mixed evenly in a ratio of 40:2:8:60, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0028] Comparative Example 1 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 23g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added into 100ml of toluene for ultrasonic dispersion; then 6.3g of polystyrene and 4.6g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 70°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; The core structure, UV-326, sodium hexametaphosphate and polyurethane were uniformly mixed in a ratio of 30:2:8:70, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0029] Comparative Example 2 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder was added to 200 ml of ethanol for ball milling, and then 1.5 g of polyvinyl pyrrolidone was added, stirred evenly, and then ultrasonically dispersed, and then centrifuged and dried to obtain modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium hexametaphosphate and polyurethane were mixed evenly in a ratio of 30:3:5:70, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0030] Comparative Example 3 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h, after the reaction is completed, centrifuge, wash and dry to obtain nano cesium tungsten bronze powder; The prepared nano-cesium tungsten bronze powder and 23g of methacryloxypropyl trimethylsiloxane were dissolved in 120ml of ethanol, and the pH value was adjusted to 8.2 by ammonia water; after filtering, washing and drying, they were added to 100ml of toluene for ultrasonic dispersion; then 8.2g of poly 3-alkylthiophene (PAT) and 4.6g of azobisisobutyronitrile were added, and stirred at a water bath temperature of 70°C for reaction. After the reaction was completed, the core structure was obtained after filtering, washing and drying; the core structure was added to 200ml of ethanol for ball milling, and then 1.5g of polyvinyl pyrrolidone was added, stirred evenly, ultrasonically dispersed, and then centrifuged and dried to obtain modified nano-tungsten bronze; The modified nano tungsten bronze, UV-326, sodium hexametaphosphate and polyurethane were mixed evenly in a ratio of 30:3:5:70, and then fed into a twin-screw extruder for melt extrusion granulation. After slicing, the window film masterbatch was obtained.
[0031] Comparative Example 4 The window film masterbatch was prepared according to the following preparation method: Take 10g of tungsten hexachloride and dissolve it in 100ml of ethanol, add 3.5g of cesium hydroxide and stir for 20min, then add 50ml of acetic acid; then react at 220℃ for 16h. After the reaction is completed, nano-cesium tungsten bronze powder is obtained after centrifugation, washing and drying; the prepared nano-cesium tungsten bronze powder, UV-326, sodium hexametaphosphate and polyurethane are mixed evenly in a ratio of 30:3:5:70, and then sent to a twin-screw extruder for melt extrusion granulation, and the window film masterbatch is obtained after slicing.
[0032] Experimental example The window film masterbatches prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to extrusion, longitudinal and transverse biaxial stretching, heat setting, relaxation, cooling, pulling and other treatments to obtain a heat insulation film with a thickness of 50 μm, and then the heat insulation film was tested for infrared blocking rate, visible light transmittance, haze, and aging resistance. The test results are shown in Table 1. Among them, the infrared blocking rate was measured by a spectrophotometer, the visible light transmittance was measured by an optical transmittance meter, the haze was measured by a haze detector, and the aging resistance was measured by a Q-SUN xenon lamp aging test box.
[0033] Table 1 Test results of Examples 1-6 and Comparative Examples 1-4
[0034] From Table 1 we can see that: According to the test results of Examples 1-6, the film prepared by using the window film masterbatch of the present invention has high visible light transmittance, infrared blocking rate and low haze, and has good aging resistance. The reason is that the grafting modification of cesium tungsten bronze by conjugated polymer polystyrene not only improves the optical properties of the product, but also inhibits the induced crystallization of cesium tungsten bronze, avoiding the problem of increased haze of the product. The core-shell structure can effectively improve the long-term service stability (aging resistance) of the product.
[0035] According to the test results of Example 1 and Comparative Example 1, compared with Example 1, the window film masterbatch in Comparative Example 1 lacks the shell structure formed by polyvinyl pyrrolidone, resulting in a decrease in the aging resistance of the product. This shows that the core-shell structure has a significant effect on improving the aging resistance of the product.
[0036] According to the test results of Example 1 and Comparative Example 2, compared with Example 1, Comparative Example 2 did not use polystyrene to modify and graft cesium tungsten bronze, resulting in a significant decrease in the final visible light transmittance and infrared blocking rate of the product. This shows that the grafting modification of the conjugated polymer polystyrene has a significant effect on improving the optical properties of the product.
[0037] According to the test results of Example 1 and Comparative Example 3, compared with Example 1, in Comparative Example 3, polystyrene is replaced by poly 3-alkylthiophene, and the optical properties of the product do not change significantly, but the haze is significantly increased, which indicates that polystyrene has a significant effect on reducing the haze of the product.
[0038] According to the test results of Example 1 and Comparative Example 4, compared with Example 1, the cesium tungsten bronze of Comparative Example 4 has not been subjected to modification treatment and core-shell coating treatment, resulting in a significant decrease in the optical performance and aging resistance of the product.
[0039] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly transparent heat-insulating and energy-saving window film masterbatch, characterized in that: The invention comprises 1 to 50 parts of modified nano tungsten bronze, 1 to 5 parts of ultraviolet absorber, 1 to 10 parts of dispersant and 35 to 100 parts of polymer carrier by weight; wherein the modified nano tungsten bronze comprises a core structure and a shell structure coated on the surface of the core structure, the core structure is nano cesium tungsten bronze modified by conjugated polymer grafting, and the shell structure is polyvinyl pyrrolidone; and the mass ratio of the core structure to the shell structure is 1:0.05 to 0.
1.
2. The highly transparent heat-insulating and energy-saving window film masterbatch according to claim 1, characterized in that: The conjugated polymer is selected from at least one of polystyrenes, polythiophenes, polyfluorenes and polybenzothiophenes.
3. The highly transparent heat-insulating and energy-saving window film masterbatch according to claim 2, characterized in that: The conjugated polymer is polystyrene with a molecular weight between 2000 and 5000.
4. The highly transparent heat-insulating and energy-saving window film masterbatch according to claim 1, characterized in that: The structural formula of the nano cesium tungsten bronze is Cs x WO3, wherein 0.01≤x≤0.3; the mass ratio of the nano-cesium tungsten bronze and the conjugated polymer is 1:0.1-0.
3.
5. The highly transparent heat-insulating and energy-saving window film masterbatch according to claim 1, characterized in that: The polymer carrier is at least one of polyethylene terephthalate, polyurethane, polyethylene and polypropylene.
6. The highly transparent heat-insulating and energy-saving window film masterbatch according to claim 1, characterized in that: The ultraviolet absorber is at least one of UV-326 and UV-1577.
7. The highly transparent heat-insulating and energy-saving window film masterbatch according to claim 1, characterized in that: The dispersant is at least one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate.
8. A method for preparing the highly transparent heat-insulating and energy-saving window film masterbatch according to any one of claims 1 to 7, characterized in that: The steps include: A proper amount of silane coupling agent and nano-cesium tungsten bronze are dissolved in ethanol, and the pH value is adjusted to between 7 and 9 by ammonia water; after filtering, washing and drying, the mixture is added into toluene and ultrasonically dispersed; then conjugated polymer and azobisisobutyronitrile are added, and stirred to react at a water bath temperature of 60 to 80°C. After the reaction is completed, the mixture is filtered, washed and dried to obtain a core structure; The core structure is added to ethanol for ball milling, and then polyvinyl pyrrolidone is added, stirred evenly, and then ultrasonically dispersed, and then centrifuged, washed, and dried to obtain modified nano tungsten bronze; The modified nano tungsten bronze, ultraviolet absorber, dispersant and polymer carrier are uniformly mixed and then sent to a twin-screw extruder for melt extrusion granulation to obtain a window film masterbatch.
9. A preparation method according to claim 8, characterized in that: The preparation steps of the nano cesium tungsten bronze include: taking an appropriate amount of tungsten hexachloride and dissolving it in ethanol, adding cesium hydroxide and stirring for a period of time, and then adding acetic acid; then reacting at a temperature of 200-260° C. for 12-24 hours, and after the reaction is completed, centrifuging, washing, and drying to obtain the nano cesium tungsten bronze.
10. Use of the highly transparent heat-insulating and energy-saving window film masterbatch according to any one of claims 1 to 7 in window films.